GENDER FEATURES OF THE FUNCTIONING OF ENGLISH INTERJECTIONS IN THE SPEECH OF MEN AND WOMEN - Genjekaraeva Saltanat (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The article is devoted to the study of the functioning of English interjections as signals of emotions in the speech of men and women belonging to the English linguacultural community, which seems especially relevant in the era of global emotionalization of the modern communicative space. The article is aimed at identifying interjection units characteristic of the speech of English men and women depending on the functions they perform. The study was carried out on the material of the book “The Diary of Bridget Jones” by Helen Fielding, which is given as a diary kept by Bridget Jones where she shares her thoughts and feelings on her daily life. The leading linguistic method in the study was the method of contextual analysis. The article identifies and substantiates qualitative and quantitative indicators of the use of English interjections in the speech of English men and women. Of all the functions performed by interjections, the most common is the emotive function, which is explained by the nature of interjections. In women's speech, the prevailing number of interjections performing the emotive function is registered, which indicates the unconscious verbalization of opposite emotions characteristic of women, while in men's speech, a greater number of interjections in the phatic function are noted. The study found that all registered interjections in the conative, phatic, hesitation functions and some of the most frequent interjections in the emotive function are gender neutral, since their qualitative composition in the speech of men and women is identical. The results presented in the article allow us to systematize the data on the functional orientation of English interjections used in the speech of English men and women.